1997
DOI: 10.1159/000201505
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Regulation of Heart Rate and QT Interval in Nonalcoholic Cirrhosis with Ascites

Abstract: Background/Aims: Autonomic neuropathy, as indicated by alterations in standard cardiovascular tests, is frequently encountered in cirrhosis. We investigated the autonomic modulation of the heart in nonalcoholic cirrhosis with ascites by evaluating the 24-hour heart rate variability (HRV), a powerful noninvasive tool to assess the sympathovagal balance of the heart. Methods: Low (LF) and high frequency (HF) components and their ratio, and time domain indexes of HRV were evaluated in 24-hour, daytime and nightti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 18 publications
1
46
0
3
Order By: Relevance
“…Whereas these findings with regard to QTc are confirmatory of previous data (12,13), our findings of a longer QTmax, QTmin, QTdisp and TpTe could appear original, owing to the fact that, to our knowledge, no study has addressed the whole spectrum of electrocardiographic markers of ventricular repolarization in cirrhotic patients. It has been suggested that the prolongation of the QT interval in cirrhotic patients is associated with a greater severity of liver disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Whereas these findings with regard to QTc are confirmatory of previous data (12,13), our findings of a longer QTmax, QTmin, QTdisp and TpTe could appear original, owing to the fact that, to our knowledge, no study has addressed the whole spectrum of electrocardiographic markers of ventricular repolarization in cirrhotic patients. It has been suggested that the prolongation of the QT interval in cirrhotic patients is associated with a greater severity of liver disease.…”
Section: Discussionsupporting
confidence: 90%
“…At ROC curves analysis, with regard to predictive value of QT indexes towards diagnosis of cirrhosis, the best cut-off for the analyzed markers of ventricular dispersion were: QTmax (sensibility: 71.99 [95% CI: 67,2e76,6], specificity: 75. 13 …”
Section: Roc Curvesmentioning
confidence: 99%
“…This is true even in the case of elevated plasma norepinephrine concentrations. This phenomenon may appear both in patients with alcoholic and non-alcoholic liver disease and correlates with the severity of cirrhosis [2,35,36].…”
Section: Chronotropic Incompetencementioning
confidence: 99%
“…In patients with cirrhosis, the lengthening of the QT interval does not seem to be related to the etiology of the liver disease, and appears both in alcoholic and non-alcoholic subjects [35,36]. The prevalence of QT prolongation is high in patients with cirrhosis and increases with the severity of the liver disease.…”
Section: Qt Interval and Dispersionmentioning
confidence: 99%
“…9,10 Other parasympathetic test results (standing to lying, Valsalva ratio, and HR variation with deep breathing) have also been shown to be abnormal in these patients. 7 Test results of sympathetic function (passive tilting and isometric exercise) are also abnormal and again point to decreased end-organ responsiveness to NE.…”
Section: Discussionmentioning
confidence: 95%